Fever of the Tuskegee Study - White, Robert (The Hastings Center report, 2016)
A commentary on “Fevered Decisions: Race, Ethics, and Clinical Vulnerability in the Malarial Treatment of Neurosyphilis, 1922–1953,” by Matthew Gambino in the July-August 2015 issue.